Review Of The Punishment Of Substitute Money And Its Consequences In The Criminal Act Of Corruption (Study Of Decision Number 51 / Pid. Sus-Tpk/2020/Pn. Smg) - Romli Mukayatsyah; Natangsa Surbakti; Muchamad Iksan (Publikasi Indonesia, 2023)
Payment of substitute money is an additional crime imposed by the panel of judges to recover state financial losses, as in Decision Number 51/Pid.Sus-TPK/2020/PN. Smg. The verdict is interesting to examine, what is the result of the panel of judges imposing additional penalties in the payment of substitute money in accordance with the purpose of the law, as well as how the view according to Islam. The study aims to analyze the consequences of the panel of judges imposing an additional criminal judgment on the payment of substitute money in Decision Number 51/Pid.Sus- TPK/2020/PN. Smg and his views according to Islam. The research is normative legal research, with a statutory approach and a conceptual approach, legal materials in the form of primary, secondary, and non-legal, the object of research is Decision Number 51 / Pid.Sus-TPK / 2020 / PN. Smg. Techniques for collecting legal materials with literature studies, with deductive analysis methods. The results of the study, as a result of which the judge's consideration did not clearly outline the calculation of state money used by the convict, imperfect defects, and non-achievement of legal objectives. Additional penalties for payment of substitute money according to Islam can be imposed on the convict because the property of Allah SWT is a mandate that must be accounted for its use